Fern Distortion Syndrome of Leatherleaf Fern in Costa Rica Symptoms, Incidence, and Severity - Kloepper, J W (Plant disease, 2010)
A syndrome has been recognized on leatherleaf fern (Rumohra adiantiformis) in Costa Rica for many years that causes widespread damage but has not been described in the literature. A full description of the syndrome, termed fern distortion syndrome (FDS), is reported here, along with evidence that FDS is a new disease and that it is associated with endophytic fluorescent pseudomonads but not with any other major groups of pathogens or pests. The main aboveground symptoms of FDS are twisting and distortions of fronds, which make the fronds unmarketable. In advanced cases of FDS, fronds are often thickened, new frond growth ceases or slows dramatically, and uneven sporulation is apparent on the underside of fronds. Symptoms of FDS belowground are reduced diameter of rhizomes and reduced overall root mass. The incidence of FDS in Costa Rica was typically over 80%, and severity typically ranged from 1.26 to 2.48 using a 0 to 3 rating scale in fields propagated vegetatively with rhizomes from fields with FDS. In contrast, in three fields planted 1.5 to 4 years previously with rhizomes derived from tissue culture, incidence and severity were markedly lower: 23 to 34% and 0.24 to 0.36, respectively. Paired sampling of symptomatic and asymptomatic plants revealed significantly greater populations of fluorescent pseudomonads inside rhizomes of symptomatic plants